2005
DOI: 10.1300/j104v40n01_03
|View full text |Cite
|
Sign up to set email alerts
|

The United Nations Classification Scheme: A Critique and Recommendations

Abstract: Anecdotal evidence suggests that dissatisfaction with the United Nations Classification Scheme (UNCS), a notational system in continuous use since 1946, has been widespread among researchers and government information specialists. Through the examination of over fourteen thousand document symbols assigned over the course of a year, this study identifies flaws in the notation that have limited its effectiveness. The criteria for this evaluation, which are drawn from both archival and library classification lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Relating more specifically to classification were critiques of some current schemes, as well as future directions for resource classification. One particularly critical discussion was aimed at the United Nations Classification Scheme -the authors suggested that decentralization in the scheme's development and maintenance was related to flaws in its simplicity, use of mnemonics, brevity, and collocation [55]. In terms of future directions, many authors came forward with ideas.…”
Section: Cataloging and Classificationmentioning
confidence: 99%
“…Relating more specifically to classification were critiques of some current schemes, as well as future directions for resource classification. One particularly critical discussion was aimed at the United Nations Classification Scheme -the authors suggested that decentralization in the scheme's development and maintenance was related to flaws in its simplicity, use of mnemonics, brevity, and collocation [55]. In terms of future directions, many authors came forward with ideas.…”
Section: Cataloging and Classificationmentioning
confidence: 99%
“…Sujanto (2012, pp. 42-43) (Griffiths, 2005;Maguire et al, 2003;Sien, 2020;Torre, 2009). Selain itu, pemanfaatan permaian untuk membantu mengajarkan berulang-ulang juga telah terbukti mampu meningkatkan kemampuan kognitif (Octavianus et al, 2022).…”
Section: Metode Pengulanganunclassified
“…Current users of UN documents may also note that the present study gives minimal attention to United Nations notation. This was done because a guide produced by the Dag Hammarskjöld Library (1997a) describes it thoroughly, and the present author has already identified its shortcomings (Griffiths, 2005).…”
Section: Introductionmentioning
confidence: 99%